Epidemiology, clinical and biological characteristics, and prognosis of critically ill COVID 19 patients: a single-center experience through 4 successive waves - Sonia Tchakerian; Noémie Besnard; Vincent Brunot; Valérie Moulaire; Nacim Benchabane; Laura Platon; Delphine Daubin; Philippe Corne; Sonia Machado; Boris Jung; Eddine Bendiab; Liliane Landreau; et al. (Pneumonia)
Abstract Objective The aim of this study was to describe the characteristics of patients admitted to the intensive care unit with severe pneumonia due to SARS-CoV-2, comparing them according to successive waves, and to identify prognostic factors for morbidity and mortality. Materials and methods This single-center retrospective observational descriptive study was conducted from March 10, 2020, to October 17, 2021. All adult patients admitted with SARS-CoV-2 pneumonia presenting acute respiratory failure were included. COVID 19 diagnosis was confirmed by RT-PCR testing of respiratory specimens. The primary endpoint was ICU mortality. Secondary endpoints were the occurrence of ventilator-associated pneumonia (VAP) or bronchopulmonary aspergillosis. Results Over the study period, 437 patients were included of whom 282 (65%) patients were ventilated for 9 [5;20] days. Among the studied population, 38% were treated for one or more episodes of VAP, and 22 (5%) for bronchopulmonary aspergillosis. ICU mortality was 26% in the first wave, then fell and stabilized at around 10% in subsequent waves (p = 0.02). Increased age, Charlson index, SOFA score and lactatemia on admission were predictive of mortality. Survival at 90 days was 85% (95% CI 82–88) and was unaffected by the presence of VAP. However, the occurrence of bronchopulmonary aspergillosis increased mortality to 36%. Conclusion In this study, we observed mortality in the lower range of those previously reported. Risk factors for mortality mainly included age and previous comorbidities. The prognosis of these critically ill Covid 19 patients improved over the four waves, underlining the likely beneficial effect of vaccination and dexamethasone.